Radial Neuritis in a Dog: Diagnosis with Assistance of Acoustic Radiation Force Impulse (ARFI) Elastography - Terrabuio, Verônica; Evangelista, Gabriela; Ercolin, Anna; Suppi, Andriele; Da Cruz, Igor; Pozzobon, Ricardo; Kommers, Glaucia; Feliciano, Marcus (Acta Scientiae Veterinariae, 2025)
Background: Neuritis is the inflammation of nerves and may be secondary to infection or autoimmune disease. It can affect any nerve of the brachial plexus, with the radial nerve being the most commonly affected in dogs, leading to clinical mononeuropathy. The diagnosis of radial neuritis is established based on clinical findings, electromyography, biopsy, and imaging techniques. In human medicine, Acoustic Radiation Force Impulse (ARFI) elastography, a non-invasive imaging technique, is employed to assess nerves, muscles, and tendons. This report aims to present a case of radial neuritis in a dog diagnosed with the assistance of ARFI elastography. Case: A 8-year-old neutered male mixed-breed dog was presented for clinical evaluation due to a 30-day history of lameness in the left thoracic limb with no history of trauma. The condition had not responded to previous treatment with anti-inflammatory and analgesic medications. On physical examination, lameness and proprioceptive deficit of the limb were observed. Hematological tests, as well as radiographs of the thoracic limb and cervical spine, revealed no significant abnormalities. B-mode ultrasonography showed a hypoechoic lesion with heterogeneous echotexture, approximately 1.0 cm in diameter, located in the region of the brachial plexus, suggestive of a nodular formation. Thickening of the dorsal nerve root adjacent to the nodule was also noted. ARFI elastography revealed that the nodular region was predominantly stiffer than the surrounding nerve tissue. Histopathological analysis of the radial nerve showed multifocal inflammatory infiltrates along its entire length, confirming the diagnosis of radial neuritis. The patient received analgesic and anti-inflammatory therapy and showed clinical progress, with improvement in lameness and reduction of the proprioceptive deficit. Discussion: There are few studies exploring ARFI elastography for the evaluation of peripheral neuropathies in veterinary medicine. In 2 cases of peripheral nerve sheath tumors in dogs, diagnosed with the aid of ARFI, the lesions exhibited areas of increased stiffness, and histopathology confirmed the diagnosis in both patients, as observed in the present case. The absence of a history of trauma in this patient further supported the diagnostic suspicion of an associated neoplastic process. In human medicine, affected nerves tend to exhibit thickening and decreased echogenicity, along with increased stiffness, which results from axonal neuropathy, demyelination, and replacement by connective tissue. Ultrasonographic evaluation of the peripheral nerves assisted in the diagnostic approach of this case, revealing thickening of the nerve branch and a suspected adjacent nodular lesion. The use of ARFI elastography provided valuable additional information for case management by indicating the increased stiffness of the nodular area. Magnetic resonance imaging (MRI) is a very useful tool for identifying peripheral nerve lesions, though it have some limitations, such as requiring sedation or anesthesia. In this context, the imaging modalities discussed in this study are more accessible, provide dynamic assessment, and do not require chemical restraint. Although rare, radial neuritis should be considered as a differential diagnosis in cases of persistent lameness and peripheral neuropathy in dogs, especially when associated with findings of increased stiffness on ARFI elastography, which stands out as a potential additional tool in the challenging diagnosis of canine mononeuropathies. Keywords: mononeuropathy, nerve sheath, diagnostic imaging, veterinary neurology, brachial plexus.